Produção do complexo quitosana-polifosfato em Rhizopus oryzae UCP 1506 utilizando substratos agroindustriais - Lima, Jaceline Maria de Negreiros (2013)
Chitosan is a natural polysaccharide originated from the deacetylation of chitin. It is soluble in acid because of the presence of amino groups, free along the polymer chain. The fungal class Zygomycetes, in particular Rhizopus oryzae, presents in its cell wall chitin and chitosan, and they may be linked through the polyphosphate or proteins and other components, respectively. The polyphosphate is a biopolymer with wide applicability in environmental biotechnology. Manipueira is the result of the process for production of pressed cassava flour and used as carbon source in fermentation processes. The corn steep liquor is a by-product of corn starch and regarded as nitrogen source. Investigations were carried out with Rhizopus oryzae in submerged fermentation for production of biomass and chitosan-polyphosphate complex, through cultivation in agro waste, cassava supplemented with corn steep liquor, using a full factorial design on 23 agitation at 150 rpm for 96h. The test with the greatest amount of biomass and chitosan was selected to perform a growth kinetics to evaluate the production of biomass and chitosan-polyphosphate complex. In this sense, was used bottles of 500ml capacity Erlenmyers containing 100mL of medium formulated being inoculated in 1-ml suspension of 107 spores per ml, incubated under orbital agitation at 150 rpm. Samples were collected every 12 hours until the period of 120h. The results showed a maximum increase of biomass with 48 hours of cultivation at pH 7.3, with maximum production of chitosan by R. oryzae 116mg / g biomass at 36h of cultivation. The polyphosphate complexed to chitosan had the highest yield in 36 h corresponding to 13mg/mg chitosan. Because the results in the production of biomass and chitosan-polyphosphate complex from Rhizopus oryzae, have become economically viable due to the use of industrial wastes to obtain these polymers.